PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA PAPAN OPERASI HITUNG BERSUSUN UNTUK MENINGKATKAN KEMAMPUAN MENGHITUNG PENJUMLAHAN DAN PENGURANGAN PADA SISWA KELAS III SD - Ni Luh Listiani Dewy; I Made Sujana Adnyana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low ability of third grade elementary school students in performing addition and subtraction. This condition was caused by learning activities that were still abstract and the lack of appropriate learning media. The purpose of this study was to improve students’ ability in addition and subtraction through the application of a contextual learning model assisted by a structured arithmetic board. This research used a classroom action research design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were third grade elementary school students. The results showed an improvement in students’ counting ability in each cycle. It can be concluded that the application of a contextual learning model assisted by a structured arithmetic board can improve students’ ability in addition and subtraction.